Faith Level of Humans to God - Syarifuddin (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This study aims to determine the Faith Level of Humans to God. This study used qualitative research. The result of study shows that the level of human belief in going to God is strongly influenced by the reality of his daily religious life. Broadly speaking, it can be classified into three groups, namely the lay class, middle class and elite class. Each group has a different level of belief in Allah according to what he believes to be the standard or perception of Allah that he knows. This lay group is also classified into three groups, namely the lowest lay class, middle class and upper class. The Lowest Laity Group is called Muttabi, namely followers who only act taqlid without thinking. What is said by his religious guide is accepted raw, as it is. In the reality of religious life, the muttabi' group is the largest group. While the Confidence Level of the Middle Lay Group has the characteristic of merely understanding around mental problems to the extent that they can understand but not yet understanding the meaning and nature of inner knowledge itself. The limited space for movement in mental problems has increased to the hobby stage and has begun to not enable the mind for worldly things, it is not functioning properly. Meanwhile, the beliefs of the upper class Laymen are generally carried by the kiai. At this level the kiai have advantage because he has little ability guide the people in terms of the study of fiqh and monotheism physically and mentally. The knowledge of a kiyai only has the nuances of charisma, which is typical, namely obeying and doing all movements according to what he got from the previous teacher.